Spinal compression in childhood : the University of Cape Town experience - Buwembo, Joseph E (Division of Neurosurgery, 2017)
Aim: A retrospective study of cases of childhood spinal compression over a 30-year period (1963-1992) was undertaken in order to determine the trend in incidence, aetiology, diagnosis, treatment and prognosis. Patients and Methods: The study includes children less than 15 years of age who were treated for spinal compression at the Red Cross War Memorial Children's Hospital, Maitland Cottage Hospital and Groote Schuur Hospital. Children who had tuberculosis of the spine without a neurological deficit, were excluded. The study also excludes dysraphism and non-compressive causes of paraplegia, such as Guillain-Barre Syndrome and poliomyelitis.